2019
DOI: 10.4081/aiua.2019.3.153
|View full text |Cite
|
Sign up to set email alerts
|

Green tea catechins for chemoprevention of prostate cancer in patients with histologically-proven HG-PIN or ASAP. Concise review and meta-analysis

Abstract: A focused, single outcome meta-analysis on the protective role of extracts of green tea catechins against prostate cancer. Randomized, placebo-controlled studies enrolling patients with a histologically confirmed diagnosis of high-grade Prostate Intraepithelial Neoplasia or Atypical Small Acinar proliferation but no prostate cancer were included. Meta-analysis for binary data was performed using Mantel-Haenszel statistics, using a random-effects model. Heterogeneity was investigated by calculating the I2. Four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 11 publications
(16 reference statements)
1
6
0
1
Order By: Relevance
“…We deemed interesting to integrate such meta-analysis with the more recent studies of Lassed et al (280 patients, risk ratio = 0.51; 95% CI: 0.14-1.82) and Sen et al, (142,196 men, of which 7036 PCa cases; risk ratio: 1.06; 95% CI: 0.98-1.14) (148,149). Our metanalysis (Figure 1) (150) shows that, in contrast to the significant data of Fei and coworkers ( 147), (risk ratio = 0.84; 95% CI: 0.71-0.98), the addition of the Lassed and Sen (148,149) trials results in a non-significant pooled risk ratio (0.89; 95% CI: 0.77-1.02). The publication bias for this pooled analysis is not significant (Egger's test: p = 0.542; Begg&Mazumdar's test: p = 0.311), but the analysis shows substantial heterogeneity (I2 = 0.69).…”
Section: Polyphenols (Alberto Trinchieri)mentioning
confidence: 84%
“…We deemed interesting to integrate such meta-analysis with the more recent studies of Lassed et al (280 patients, risk ratio = 0.51; 95% CI: 0.14-1.82) and Sen et al, (142,196 men, of which 7036 PCa cases; risk ratio: 1.06; 95% CI: 0.98-1.14) (148,149). Our metanalysis (Figure 1) (150) shows that, in contrast to the significant data of Fei and coworkers ( 147), (risk ratio = 0.84; 95% CI: 0.71-0.98), the addition of the Lassed and Sen (148,149) trials results in a non-significant pooled risk ratio (0.89; 95% CI: 0.77-1.02). The publication bias for this pooled analysis is not significant (Egger's test: p = 0.542; Begg&Mazumdar's test: p = 0.311), but the analysis shows substantial heterogeneity (I2 = 0.69).…”
Section: Polyphenols (Alberto Trinchieri)mentioning
confidence: 84%
“…The objective of this review is to summarize the current research on the safety and effectiveness of GTCs in modulating prostate carcinogenesis based on population, in vitro, pre-clinical and early clinical trials. Although previous reviews have examined the pre-clinical and early phase trials of GTCs and PCa [ 29 , 30 , 31 , 32 , 33 ], our review will additionally identify discrepancies in the results of previous studies and examine the early and evolving data on the role of the gut microbiome in modulating the bioavailability, safety, and anticarcinogenic properties of GTCs in prostate carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…17) Furthermore, several phase II clinical trials with GTE indicated its preventive effects toward cancer development for patients with preneoplastic diseases in the prostate and oral cavity. [18][19][20] All results indicated that "Primary cancer prevention" for the general population can be achieved by drinking 10 cups of green tea/d to delay cancer onset (Fig. 2).…”
Section: Primary Cancer Prevention With Egcg and Green Teamentioning
confidence: 95%